Притчевая специфика киноповести «Родник для жаждущих» И. Драча - Nikoriak, Nataliia (Česká asociace slavistůve spolupráci s Filozofickou fakultou Masarykovy univerzity, 2021)
The film story Spring for the Thirsty by I. Drach is a text that is close in its parameters to the peculiarities of parable poetics. Direct instruction and unambiguous didacticism, which is characteristic of the parable genre, are strengthened by philosophical reflection (from prologue to epilogue). The image of the main character is depicted, above all, through the psychological motivation of his actions, with some features of certain idealization of the image in a dichotomous tandem “fathers and children”. In the aspect of parable specifics, particular emphasis is laid on the tendency towards generalization, as well as on a peculiar (marked with a high extent of conventionality) principle of abstraction of ideas. The author actively reproduces dreams or visions (metaphorical, symbolic), which are closely related to the main events of the text. With the help of this technique, he conveys the inner experiences, subconsciousness, fears or hopes of the old Levko, at the same time erasing the boundaries between reality and unreality. The application of such a two-dimensionality in the narrative of the text, strengthened by the active use of intertextual and intermediate codes, offers a deep philosophical implication inherent in the parable.
Keywords: film story; film parable; intertext; intermedial code; Spring for the Thirsty; I. Drach